Fear Of Missing Out (FOMO) dan Psychological Well Being (PWB) dalam menggunakan media sosial (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to obtain empirical data regarding the relationship between Fear of Missing out and the Psychological well being of adolescents using social media. Subjects in this study were 100 subjects from a total population of 121 high school students YPBK 1, Surabaya. The sampling technique in this study used an incidental sampling technique. Based on the results of the non- parametric Spearman Rho correlation test, it was obtained rxy = -0.407 with a significance (p) of 0.00<0.01, it can be said that there is a significant negative correlation between Fear of Missing out and the psychological well being. This means that the high Fear of Missing out will lead to lower individual Psychological well being in using social media. Data analysis techniques were assisted by using IBM Statistics version 20 for windows. Penelitian ini bertujuan untuk memperoleh data empiris mengenai hubungan antara Fear of Missing out dengan Psychological well being remaja menggunakan media sosial. Subjek dalam penelitian ini berjumlah 100 Subjek dari jumlah populasi sebanyak 121 siswa SMA YPBK 1, Surabaya. Teknik sampling dalam penelitian ini menggunakan teknik isidentil sampling. Berdasarkan hasil uji korelasi teknik non parametric Spearman Rho diperoleh rxy = -0,407 dengan signifikansi (p) 0,000 < 0,01, dapat dikatakan bahwa terdapat korelasi negatif yang signifikan antara Fear of Missing out dengan psychological well being. Artinya, Fear of Missing out yang tinggi menyebabkan semakin rendahnya Psychological well being individu dalam menggunakan media sosial. Teknik analisis data dibantu dengan menggunakan IBM Statistics versi 20 for windows.